2007
DOI: 10.1063/1.2767829
|View full text |Cite
|
Sign up to set email alerts
|

Hard x-ray source for flash radiography based on a 2.5kJ plasma focus

Abstract: Effective hard x-ray spectrum of a tabletop Mather-type plasma focus optimized for flash radiography of metallic objects J. Appl. Phys. 102, 123303 (2007) Hard x-ray source for flash radiography based on a 2.5 kJ plasma focus A compact tabletop plasma focus suitable for hard x-ray imaging applications is presented. The hard x-ray emission was characterized by means of an effective energy analysis, based on images obtained with a single shot. The effective energy of the radiation was estimated to be around 83 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The pinching evidence has been observed in the PF devices operated at very low bank energies of ≈100 J (Soto et al 2001), of 32-102 J (Silva et al 2002), of 50 J (Moreno et al 2003), of 50-70 J (Silva et al 2004) and of 58-160 J (Hassan et al 2006). The generation of extreme ultraviolet (Mohanty et al 2006) as a compact and competent source for lithography, emission of soft x-rays (Mohammadi et al 2007) useful for lithography and production of hard x-rays (Moreno et al 2006, Lorenzo et al 2007 for flash radiography have also been reported. It is observed that none of these recent PF devices uses a sealed plasma chamber for long duration and multi-shot operations with a single gas filling.…”
Section: Introductionmentioning
confidence: 82%
“…The pinching evidence has been observed in the PF devices operated at very low bank energies of ≈100 J (Soto et al 2001), of 32-102 J (Silva et al 2002), of 50 J (Moreno et al 2003), of 50-70 J (Silva et al 2004) and of 58-160 J (Hassan et al 2006). The generation of extreme ultraviolet (Mohanty et al 2006) as a compact and competent source for lithography, emission of soft x-rays (Mohammadi et al 2007) useful for lithography and production of hard x-rays (Moreno et al 2006, Lorenzo et al 2007 for flash radiography have also been reported. It is observed that none of these recent PF devices uses a sealed plasma chamber for long duration and multi-shot operations with a single gas filling.…”
Section: Introductionmentioning
confidence: 82%
“…[3][4][5][6][7][8][9]. A most comprehensive review of the state of the art can be found in Bernard et al 10 The approach followed in the present work is to use the electron beam generated backward by the Plasma Focus device to generate xrays upon conversion of the beam onto a metal target.…”
mentioning
confidence: 99%
“…The soft X-ray emission from dense plasma focus is according to two mechanisms: linear radiation and continuum radiation (recombination and Bremsstrahlung radiation) [18][19][20]. The hard X-rays are also produced by the collisions of electron beams resulting from the collapse of the plasma pinch with the anode [21][22][23].…”
Section: Introductionmentioning
confidence: 99%